Changes in attitudes to vaccination as a result of the COVID-19 pandemic: A longitudinal study of older adults in the UK. - Allyson J Gallant; Louise A Brown Nicholls; Susan Rasmussen; Nicola Cogan; David Young; Lynn Williams (PLoS ONE, 2021)
Background The rapid development of COVID-19 vaccines has brought an unprecedented focus on public attitudes to vaccines, with intention to accept a COVID-19 vaccine fluctuating during the pandemic. However, it is unclear how the pandemic may influence attitudes and behaviour in relation to vaccines in general. The aim of the current study is to examine older adults' changes in vaccination attitudes and behaviour over the first year of the pandemic. Methods In February-March 2020 (before the first COVID-19 national lockdown in the UK), 372 older adults (aged 65+) provided sociodemographic information, self-reported influenza vaccine uptake, and completed two measures of vaccination attitudes: the 5C scale and the Vaccination Attitudes Examination Scale. One-year later, following rollout of COVID-19 vaccines to older adults, participants provided information on their COVID-19 and influenza vaccine uptake in the previous 12 months, and completed the 5C and VAX scales again. Paired samples t-tests were used to examine changes in vaccination attitudes over time. Results Almost all participants (98.7%) had received at least one dose of a COVID-19 vaccine, and a significant increase in influenza uptake was identified (83.6% in 2020 to 91.6% in 2021). Complacency, mistrust of vaccine benefit, concerns about commercial profiteering, and constraints to vaccination had significantly decreased between Time 1 and Time 2, and collective responsibility had significant increased. However, calculation and worries about unforeseen future effects had increased, indicating that participants now perceived higher risks related to vaccination and were taking a more deliberative information-seeking approach. Conclusion The results show significant changes in vaccination attitudes across the pandemic. These changes suggest that while older adults became less complacent about the importance of vaccines, concerns about potential risks associated with vaccination increased. It will be important for public health communication to address these concerns for all vaccines offered to this group.